Long noncoding RNA HULC modulates the phosphorylation of YB‐1 through serving as a scaffold of extracellular signal–regulated kinase and YB‐1 to enhance hepatocarcinogenesis. Issue 5 (22nd March 2017) - Li, Dan; Liu, Xuefeng; Zhou, Jian; Hu, Jie; Zhang, Dongdong; Liu, Jing; Qiao, Yanyan; Zhan, Qimin
Abstract : Dysregulated expression of long noncoding RNAs has been reported in many types of cancers, indicating that it may play a critical role in tumorigenesis. The long noncoding RNA highly up‐regulated in liver cancer (HULC) was first characterized in hepatocellular carcinoma. However, the detailed mechanisms of HULC remain unclear. Here, we demonstrate a novel mechanism by which long noncoding RNA plays oncogenic roles through modulating the phosphorylation status of its interaction protein. First, we validated the markedly increased expression levels of HULC in hepatocellular carcinoma tissues compared to their adjacent noncancerous tissues. Furthermore, up‐regulation of HULC was correlated with grading and overall survival. Meanwhile, HULC could promote cell proliferation, migration, and invasion in vitro and inhibit cisplatin‐induced apoptosis. Moreover, we show that HULC specifically binds to Y‐box binding protein 1 (YB‐1) protein both in vitro and in vivo . YB‐1 is a major component of translationally inactive messenger ribonucleoprotein particles which keeps mRNA in a silent state. Our study further demonstrated that HULC could promote the phosphorylation of YB‐1 protein, which leads to the release of YB‐1 from its bound mRNA. As a consequence, translation of silenced oncogenic mRNAs would be activated, including cyclin D1, cyclin E1, and matrix metalloproteinase 3. In addition, we found that HULC promotes the phosphorylation of YB‐1 protein mainly through extracellular signal–regulated kinase. Conclusion : We demonstrate that HULC promotes the phosphorylation of YB‐1 through the extracellular signal–regulated kinase pathway, in turn regulates the interaction of YB‐1 with certain oncogenic mRNAs, and consequently accelerates the translation of these mRNAs in the process of tumorigenesis. (Hepatology 2017;65:1612‐1627)